Comparison between manual analysis and STAAD.Pro analysis of continuous beam based on Eurocode 2 - Siti Nur Sakinah Sulaiman, 1995-, author; Roslli Noor Mohamed, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2018